Slimbridge Church
This is one of the few complete examples of an early English parish church. The deeply carved capitals and the use of pointed arches are typical, but there is not the same richness of detail evident in the major Cathedrals built during the same period. Most of the wealth was concentrated in monastic or cathedral foundations, and the parish church was usually contented with additions or extensions to its nave.